What makes a fertile sperm? Unique molecular attributes of stallion fertility. Issue 4 (October 2019) - Griffin, Róisín A; Baker, Mark; Aitken, Robert John; Swegen, Aleona; Gibb, Zamira
Abstract : Stallions experience lower per-cycle conception rates compared to other livestock species, largely because they are selected for breeding based on athletic prowess and not reproductive fitness. Mares are seasonal breeders, and pregnancies cannot be detected until 10–14 days post cover via transrectal ultrasonography. This means the detection of stallion fertility fluctuations is delayed by at least 2 weeks, which within the short breeding season employed by the thoroughbred horse breeding industry, can prove quite costly. For these reasons, there is increased demand for robust laboratory assays aimed at the accurate assessment of stallion fertility. This paper reviews our existing knowledge concerning the molecular mechanisms that underpin the functional competence of stallion spermatozoa, highlighting the relative importance of oxidative stress, DNA damage, sperm proteomics and RNA profile. We also consider the way in which fundamental improvements in our understanding of stallion sperm biology are informing the identification and development of possible biomarkers of fertility and thus avenues for the development of specific assays for fertility prediction.